Toward a More Ecologically Valid Measure of Speech Understanding in Background Noise - Jerger, James; Greenwald, Ralf; Wambacq, Ilse; Seipel, Amanda; Moncrieff, Deborah (Journal of the American Academy of Audiology, 2000)
In an attempt to develop a more ecologically valid measure of speech understanding in a background of competing speech, we constructed a quasidichotic procedure based on the monitoring of continuous speech from loudspeakers placed directly to the listener's right and left sides. The listener responded to the presence of incongruous or anomalous words imbedded within the context of two children's fairy tales. Attention was directed either to the right or to the left side in blocks of 25 utterances. Within each block, there were target (anomalous) and nontarget (nonanomalous) words. Responses to target words were analyzed separately for attend-right and attend-left conditions. Our purpose was twofold: (1) to evaluate the feasibility of such an approach for obtaining electrophysiologic performance measures in the sound field and (2) to gather normative interaural symmetry data for the new technique in young adults with normal hearing. Event-related potentials to target and nontarget words at 30 electrode sites were obtained in 20 right-handed young adults with normal hearing. Waveforms and associated topographic maps were characterized by a slight negativity in the region of 400 msec (N400) and robust positivity in the region of 900 msec (P900). Norms for interaural symmetry of the P900 event-related potential in young adults were derived.Abbreviations: CVC = consonant-vowel-consonant, EEG = electroencephalic, ERP = event-related potential, ISI = interaural symmetry index, VEOG = vertical electro-oculography
Keywords: Dichotic; event-related potential; speech competition